From training to workflow: a mixed-methods assessment of integration of Doppler into maternity ward triage and admission in Tanzania. (2019) - Jennings, Mary Carol; Bishanga, Dunstan R.; Currie, Sheena; Rawlins, Barbara; Tibaijuka, Gaudiosa; Makuwani, Ahmad; Ricca, Jim; John, John; Mpogoro, Filbert; Abwao, Stella; Njonge, Lusekelo; Zougrana, Jeremie; et al.
No abstract available